2013
DOI: 10.1002/cncr.28431
|View full text |Cite
|
Sign up to set email alerts
|

Cancer care for individuals with schizophrenia

Abstract: Individuals with schizophrenia are a vulnerable population that has been relatively neglected in health disparities research. Despite having an equivalent risk of developing most cancers, patients with schizophrenia are more likely to die of cancer than the general population. Cancer care disparities are likely the result of patient-, provider-, and systems-level factors and influenced by the pervasive stigma of mental illness. Individuals with schizophrenia have higher rates of health behaviors linked with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
265
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(284 citation statements)
references
References 72 publications
10
265
1
2
Order By: Relevance
“…Schizophrenia patients have an approximately 20% reduced life expectancy compared to the general population (Hennekens et al, 2005) with smoking-related diseases being major contributors to premature death (Irwin et al, 2014;McClave et al, 2010;Ruther et al, 2014). Identifying the patterns of smoking and its correlates in schizophrenia and implementing effective control strategies to reduce its prevalence and harmful consequences is important for policymakers and health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia patients have an approximately 20% reduced life expectancy compared to the general population (Hennekens et al, 2005) with smoking-related diseases being major contributors to premature death (Irwin et al, 2014;McClave et al, 2010;Ruther et al, 2014). Identifying the patterns of smoking and its correlates in schizophrenia and implementing effective control strategies to reduce its prevalence and harmful consequences is important for policymakers and health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…10,[18][19][20][21] The reason for the discrepancy between cancer incidence and mortality in patients with schizophrenia remains unclear; 20 however, potential related factors may include delayed diagnosis and lower likelihood of receiving cancer care. Several studies have found a difference in access to cancer care between patients with schizophrenia and the general population, 22 with those with schizophrenia being less likely to receive screening for cancer. [23][24][25][26] A few studies suggested that people with schizophrenia may have undergone delays in the diagnosis of cancer and initiation of treatment.…”
mentioning
confidence: 99%
“…SPMI is associated with premature mortality across all age groups [1,2]. Despite common misassumptions that most individuals with SPMI die prematurely from violence and suicide, the majority of excess mortality is due to chronic diseases such as cancer, heart disease, chronic obstructive pulmonary disease, and dementia [3,4]. Excess mortality from chronic disease is multifactorial; increased substance use and its medical sequelae, decreased engagement with preventive health care, and poor access to medical care all contribute [4].…”
mentioning
confidence: 99%
“…Despite common misassumptions that most individuals with SPMI die prematurely from violence and suicide, the majority of excess mortality is due to chronic diseases such as cancer, heart disease, chronic obstructive pulmonary disease, and dementia [3,4]. Excess mortality from chronic disease is multifactorial; increased substance use and its medical sequelae, decreased engagement with preventive health care, and poor access to medical care all contribute [4]. Patients with schizophrenia, for example, have a similar incidence of most cancers to the general population, but these patients have up to a two-fold risk of dying of their disease due to under-detection and under-treatment [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation